Holiday or vacation? The processing of variation in vocabulary across dialects. Issue 3 (15th March 2016) - Martin, Clara D.; Garcia, Xavier; Potter, Douglas; Melinger, Alissa; Costa, Albert
ABSTRACT: Native speakers with different linguistic backgrounds differ in their usage of language, and particularly in their vocabulary. For instance, British natives would use the word "holiday" when American natives would prefer the word "vacation". This study investigates how cross-dialectal lexical variation impacts lexical processing. Electrophysiological responses were recorded, while British natives listened to British or American speech in which lexical frequency dominance across dialects was manipulated (British versus American vocabulary). Words inconsistent with the dialect of the speaker (British words uttered by American speakers and vice versa) elicited larger negative electrophysiological deflections than consistent words, 700 ms after stimulus onset. Thus, processing of British words was easier when listening to British speakers and processing of American words was easier when listening to American speakers. These results show that listeners integrate their knowledge about cross-dialectal lexical variations in vocabulary as speech unfolds, as it was previously shown for social lexical variations.